Modulation of Emotional Conflict Processing by High-Definition Transcranial Direct Current Stimulation (HD-TDCS) - Kuehne, Maria; Schmidt, Katarina; Heinze, Hans-Jochen; Zaehle, Tino (Frontiers in Behavioral Neuroscience, 2019)
Cognitive control is characterized by selective attention to relevant stimuli while irrelevant, distracting stimuli are inhibited. While the classical color word Stroop task was implemented to investigate the processes of cognitive control, a variant of it – the face-word Stroop task – allows for directly investigating processes of emotional conflict control. It is thought that the prefrontal cortex (PFC) is especially involved in processes of cognitive control, while the rostral cingulate is mainly associated with the resolution of emotional conflict. In recent years, the role of the dorsolateral PFC (DLPFC) during the performance of the classical Stroop was investigated by means of transcranial direct current stimulation with divergent results. However, investigations to the causal role of the DLPFC during emotional conflict processing are rare. For this purpose, we used a combined HD-tDCS/EEG setting to investigate the impact of anodal stimulation of the left DLPFC on behavioral and electrophysiological responses during an emotional face-word Stroop task. Our results show that anodal stimulation of the left DLPFC increases the behavioral interference effect and modulates brain response to emotional facial expressions during a face-word Stroop task.